Pengaruh Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Hijab Wanda Scarf Serang - Suyatna, Riki Gana; Marni, Marni; Novianti, Ola; Sarmila, Sarmila; Mutiara, Lulu; Osama, Osama (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the effect of brand image and product quality on purchasing decisions of Wanda Scarf hijab products in Serang City. The rapid growth of the hijab fashion industry has intensified competition among brands, requiring business owners to build a strong brand image and maintain product quality to attract consumers. A positive brand image and good product quality are considered important factors influencing consumers’ purchasing decisions. This research employs a quantitative approach using an associative method. Data were collected through questionnaires distributed to Wanda Scarf consumers. Multiple linear regression analysis was applied, along with t-test and F-test to examine the hypotheses. The results indicate that brand image and product quality have a positive and significant effect on purchasing decisions, both partially and simultaneously. These findings suggest that improving brand image and product quality can increase consumers’ purchasing decisions toward Wanda Scarf hijab products